ASSIMILATION OF PRODUCTION OF COLD-W'ORKED LOW-CARBON WIRE WITH THREESIDED DIE-ROILED SECTION FOR REINFORCEMENT OF CONCRETE CONSTRUCTIONS AT RUP “BMZ” - A. N. Savenok; A. V. Zinovenko; G. N. Katylkov; O. N. Leshkevich (Литьë и металлургия)
The production of cold-worked reinforcing wire with diameter 4 and 5 mm is assimilated at RUP “BMZ”